Academy of Management News and Notes (Academy of Management Journal, 1960)
Provides an update related to management as of 1960. Management courses offered by the Society for the Advancement of Management; Promotion of Professor William E. Hurley at the Ohio State University; Resignation of Stanley Vance at Kent State University; List of research projects and books submitted to the journal.